Germanizmy leksykalne wśród Barbaryzmów i dziwolągów językowych - Mędelska, Jolanta; Cieszkowski, Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
The authors of the article discuss linguistic material excerpted from a small-scale book written by Józef Bliziński and entitled Barbaryzmy i dziwolągi językowe [Barbarisms and linguistic oddities] published in Cracow towards the end of the nineteenth century. The source material for the analysis and the main focus of the authors are the borrowings from the German language. The book, written by an eminent comedy writer, deals with the correctness and the accepted standards of the Polish language in the then Austrian-partitioned Poland. As one might expect, since the target readers for this linguistic handbook were the inhabitants of Galicia in Eastern Europe, it would include mostly Germanisms. The analysis of the book, however, has proved that German loan words in Blizinski’s book are rather scarce. Nearly a half from the fifteen words considered as Germanisms by Blizinski could have French origins (although they might have been borrowed to the Polish language through the German medium). On the other hand, the book includes six words that may be Germanisms but that were not assigned by the author to the group of German borrowings.